Pengaruh Metode Cooperative Integrated Reading And Composition (Circ) Terhadap Kemampuan Berfikir Kritis Siswa Pada Pelajaran Biologi Kelas Viii Mts. Mu’allimin Nw Pancor Tahun Pembelajaran 2013/2014. - Nuraini Nuraini (Cocos Bio, 2016)
Biology learning is generally still less active and mostly uses conventional learning, which has an effect on the decline of students' critical thinking skills and absorption or student mastery of the material being taught. The purpose of this study was to determine the effect of cooperative integrated reading and composition (CIRC) methods on students' critical thinking skills in the biology class of viii mts. mu'allimin Nw pancor 2013/2014 learning year.        This type of research is experimental research with experimental design design (pretest-posttest control group) population of this study were all students of class VIII MTs. Mualimin NW Pancor. The sample in this study was simple random sampling. Data collection techniques use tests, in the form of 5 questions. Data analysis techniques look at critical thinking skills using prerequisite tests (normality, homogeneity test) and hypothesis testing that is by t-test (t-test)       The results of the research obtained are the posttest average values in the 77.53 experimental class and the 70.92 control class and the results of the normality test are the experimental class and the normally distributed controls. To test the hypothesis used the t-test formula. obtained by tcount t table (4,166 1,874). Then it can be concluded that the use of integrated cooperative reading and composition (CIRC) learning methods has an effect on students' critical thinking skills in the biology class viii mts.muâ€™allimin Nw pancor learning year 2013/2014.